“They’re Meant for Men”: The Gendered Meaning of “Evidence-Based Practices” in Prison - Gorga, Allison (Women & criminal justice, 2025)
Drawing upon 38 interviews with prison staff, administrators, service providers, and volunteers in Iowa, I examined the ways in which prison stakeholders engaged with “evidence-based practices” (EBP). I discovered that many of the stakeholders were both receptive and critical of EBP, and that gendered organizational practices could explain some of this complexity. Gendered hierarchies across the correctional system created valued and devalued sources of knowledge, which shaped women’s prison employees’ perception of and critique of “gender neutral” EBP. For example, organizational practices reinforced ideas of gender difference which facilitated receptivity to gender specific EBP (such as gender responsivity), while “gender neutral” programs that were part of statewide initiatives were received with skepticism and constantly challenged. Policy suggestions for improving the delivery of evidence-based practices are also discussed.